1992
DOI: 10.1063/1.529875
|View full text |Cite
|
Sign up to set email alerts
|

Constraints of the Kadomtsev–Petviashvili hierarchy

Abstract: For the Kadomtsev–Petviashvili (KP) hierarchy constructed in terms of the famous Sato theory, a ‘‘k constraint’’ is proposed that leads the hierarchy to the nonlinear system involving a finite number of dynamical coordinates. The eigenvalue problem of the k-constrained system is naturally obtained from the linear system of the KP hierarchy, which takes the form of kth-order polynomial coupled with a first-order one, thus we are able to derive the correspondent Lax pair, recursion operator, bi-Hamiltonian struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
197
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(202 citation statements)
references
References 16 publications
3
197
0
2
Order By: Relevance
“…The modified flows are defined on the phase space Θ by pulling back the Hamiltonians H Q j in (8) by means of the map µ. For reasons explained in [9] (see also [1,2]), if s = 0 the factor…”
Section: Modifications Of Extended Gelfand-dickey Hierarchiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The modified flows are defined on the phase space Θ by pulling back the Hamiltonians H Q j in (8) by means of the map µ. For reasons explained in [9] (see also [1,2]), if s = 0 the factor…”
Section: Modifications Of Extended Gelfand-dickey Hierarchiesmentioning
confidence: 99%
“…There have been several papers over the last few years devoted to systems of the above type [1][2][3][4][5][6][7][8]. It was shown in [9] how hierarchies with a Lax operator of the form in (1) can be obtained by the Drinfeld-Sokolov (DS) reduction method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Either (2+1)-dimensional soliton equations [1], [2] or (1+1) -dimensio -nal soliton equations [3], [4] can be decomposed into two compatible finite-dimensional integrable systems. It is known that a crucial idea in carrying out symmetry constraints is the nonlinearization of Lax pairs for soliton hierarchies.…”
Section: Introductionmentioning
confidence: 99%
“…The new type of reduced Kadomtsev-Petviashvili (KP) hierarchy, called the constrained KP hierarchy, was introduced in [KSS91,KS92], where it was observed that the YO hierarchy can be obtained as a constrained KP hierarchy (and this was used in [Che92] to find its bi-Poisson structure). A more general s-vector constrained KP hierarchy was introduced in [SS93], where it was shown that the multi-component YO hierarchy, studied in [Ma81], can be obtained by this construction.…”
mentioning
confidence: 99%